Pengetahuan Remaja Tentang Personal Hygiene Saat Keputihan di SMP Negeri 1 Maduran - Ida Susila; Khusnul Nikmah; Kholifatul Ummah; Risma Wardah Malichah (PT Nuansa Fajar Cemerlang, 2025)
Personal hygiene education for adolescents during vaginal discharge needs to be taught as early as possible to prevent infectious diseases caused by poor hygiene during vaginal discharge. The purpose of this study was to determine the personal hygiene of adolescent girls with vaginal discharge. Fifty respondents met the inclusion criteria through a total sampling method. Descriptive analysis was used. The study's characteristics were age, with the majority being 13 years old. Forty-six (46%) students had poor knowledge about personal hygiene. The type of vaginal discharge identified was abnormal, with 54 respondents (54%). Limited access to information and facilitators at the educational institution contributed to this lack of knowledge among the students. Based on the study results, researchers collaborated with health agencies and schools to conduct outreach activities to improve adolescent girls' knowledge about personal hygiene during vaginal discharge.